Sorsogon waterfront development project - Francisco-Gegajo, Luisita (Quezon City College of Architecture, University of the Philippines Diliman, 2012)
Waterfront development project makes many local and foreign toursit and visitors attractive and favorite destinations. It can provide new areas of high quality public open space and popular venues for social activities. Most of the local government units are now trying to develop and using different schemes on how waterfront projects are realized in their city or towns. This study provides insights in the conceptualization of the Sorsogon City waterfront development project. Sorsogon City Waterfront Development Project through the process of reclamation is the solution to the present socio-economic conditions of the city especially at the waterfront area. The total development is equivalent to 73.27 hectares along barangay Bitan-o / Dalipay, Talisay, Sirangan and Sampaloc. This development are as follows; the business center and leisure park center this will provide opportunity to generate and upgrade the economic activities of the city. The expansion of the commercial center along the circumferential roads and at the waterfront reclaimed area will beat with activity of downtown and urban retail streets that would encourage rich, exciting urban interrelations. In upgrading the present port area will open an avenue for employment, small scale business opportunities, local manufacturer may introduce their products to the different parts of the country and allowing motorized banca to transporting goods and passengers from the coastal areas of the different municipalities will eventually bring the different coastal communities closer to the capital city. By having a net work of City Park, open space, playgrounds and sports facilities will develop and encouraged a healthful lifestyle for Sorsoganons. The waterfront development project of Sorsogon City will be one of the famous tourist destinations in the country and in the world.
Vita.
Thesis (Master of Architecture)--University of the Philippines Diliman.